Enhancing the capability of online teaching for elementary school teacher through interactive video making training - Yuita Arum Sari; Randy Cahya Wihandika; Sigit Adinugroho; Indriati Indriati; Putra Pandu Adikara (Community Empowerment, 2022)
The strategies and learning mechanisms that have been widely used up until now have changed as a result of the Covid-19 pandemic. Learning from home (BDR) activities are used to replace face-to-face learning activities. Effective implementation of BDR requires information technology skills, especially the use of learning support software. Thus, it is imperative that teachers receive training in the use of learning support software in order to advance their abilities to teach online effectively and efficiently. In this community service, training activities for making creative teaching materials were carried out for elementary school teachers. The creative teaching material is in the form of animation, so that it attracts the interest of students and is expected to increase the effectiveness of online learning. This community service activity begins with a pre-test, continues with the delivery of material, and ends with the provision of a post-test and questionnaire. The evaluation's findings revealed that participants' skills had improved when learning support hardware and instructional videos were introduced.